Diamond interest electronic commerce website - Tian, Yuh Ming (University Malaysia Sarawak, UNIMAS., 2005)
Nowadays, the use of electronic commerce (e-commerce) to conduct business is growing rapidly. Many organizations have moved towards the modern way to computerize transaction processes. Information Technology (IT) have proved to be very popular as it support online shopping, transaction, daily work's productivity and reduce paperwork, efficiently and effectively. Hence, Diamond Interest E-Commerce Website is developed. It is an automated system to help the company to manage daily tasks and track sales easily.